Design and Implementation of Robot Abu Robocon Using Joystik Wireless Based on Extrasenory Percepsion - Minsandi, Ayub; Saputra, Rifaldo; Dwi Kurniawan, Bintang; Simanullang, Aldi; Aprilianty, Resti; Rahman, Aulia; Khulkhairat, Delvira; Yuhendri, Muldi (Department of Electrical Engineering Universitas Negeri Padang, 2024)
The development of technology, particularly in the field of robotics, is increasingly influencing various aspects of life, including the organization of robot contests which are attracting more participants. The Indonesian Robot Contest (KRI) and the ABU Robocon Indonesia Robot Contest (KRAI) are competitions involving broad participation from across the Asia Pacific. Robots in these competitions are controlled using instructions from operators, where the use of wireless joysticks has become very common to enhance control efficiency. However, in practice, issues such as signal connection loss often occur, especially when using PlayStation 2 joysticks with limited signal range. This study aims to develop a more stable remote control system using an ATmega 2560 microcontroller and an ESP32 to provide Bluetooth signals. The research method used is experimental, including the stages of analysis, design, implementation, and evaluation. The results show that the control system with an ESP-based PS4 joystick can increase the control range up to 15 meters with more stable connectivity compared to the previous system. Testing also indicates that precise IP address assignment can prevent signal interference from other devices, making this system effective for use in robotics competitions